Evaluasi Program Ekstrakurikuler D’valist pada Divisi Perpustakaan Putri Pesantren Darunnajah 2 Cipining - Intan Febriani; Anjaludin; Mahmun Nurudin (Journal on Education, 2025)
There are several obstacles in the implementation of the D’VALIST extracurricular program in the Girls’ Library Division of Pesantren Darunnajah 2 Cipining, including low student participation, limited and rarely updated book collections, lack of innovation in activities, as well as scheduling conflicts with other pesantren activities. These obstacles require evaluation and improvement so that the D’VALIST program can run more effectively, considering its important role in enhancing literacy, creativity, and character building among students. This research is a qualitative study conducted within the Girls’ Student Affairs Department. Data collection methods included interviews, observations, and documentation. The research subjects were the Director of Student Affairs, the dormitory head, library supervisors, and female students who are members of D’Valist. The research was conducted at Pesantren Darunnajah 2 Cipining. The objectives of this study are to identify: (1) the relevance of the D’VALIST program to students’ needs (context), (2) the readiness of human resources and facilities (input), (3) the process of implementing D’VALIST activities (process), and (4) the results or impact of the program on students’ reading interest and skills (product). The findings show that in terms of context, the D’VALIST program aligns with the pesantren’s vision of building a literacy culture. In terms of input, the library facilities are fairly adequate, but student participation remains low and the book collection lacks variety. In terms of process, activities are implemented but not consistently, as they often overlap.